Corporate tax policy and international mergers and acquisitions: is the tax exemption system superior - Johannes Becker; Clemens Fuest (Center for Economic Studies and ifo Institute (CESifo), 2007)
In this paper we ask whether recent claims that the US government should switch from the tax credit system to the exemption system are justified. We study corporate taxation in a model where international capital flows are either greenfield investment projects or acquisitions of existing firms, and where investment is motivated by either cost reduction or market entry reasons. The paper asks how corporate taxation affects the international allocation of capital under different double taxation regimes. We find that the standard view on international taxation only prevails in the case of cost driven greenfield investment. In all other cases the deduction system is no longer optimal from a national perspective and the foreign tax credit system fails to ensure neutrality. However, the desirability of the tax exemption system has to be qualified. We show that the cross border cash flow tax system dominates the exemption system in terms of optimality properties.
Keywords: H25; F23; 330; Körperschaftsteuer; Unternehmensbesteuerung; Doppelbesteuerung; Steuerliches Anrechnungsverfahren; Steuerbegünstigung; Besteuerungsgrundsatz; Internationale Kapitalmobilität; USA